Clinical course and prognostic factors of COVID-19 infection in patients with chronic inflammatory-rheumatic disease: A retrospective, case-control study - Kemal Nas,; Ertuğrul Güçlü,; Yaşar Keskin,; Gamze Dilek,; Mehtap Kalçık Unan,; Nurselin Can,; İbrahim Tekeoğlu,; Ayhan Kamanlı, (Archives of Rheumatology, 2023)
Objectives: This study aims to investigate the prognosis of novel coronavirus disease-2019 (COVID-19) infection in patients with the chronic inflammatory-rheumatic disease and evaluate the effects of immunosuppressive drugs on the prognosis, clinical characteristics, laboratory findings and hospitalization periods of the rheumatic patients with COVID-19 infection. Patients and methods: Between April 2020 and March 2021, a total of 101 patients (30 males, 71 females; mean age: 48±14.4 years; range, 46 to 48 years) with the rheumatic diseases diagnosed with COVID-19 infection were included. A total of 102 age- and sex-matched patients (35 males, 67 females; mean age: 44±14.4 years; range, 28 to 44 years) who were diagnosed with COVID-19 infection and had no history of rheumatic disease in the same period were included as the control group. Data including demographic characteristics of the patients, presence of any symptoms of COVID-19 disease, laboratory data at the time of diagnosis, and treatments administered were collected. Results: The rate of hospitalization was higher in 38 (37%) patients without rheumatic diseases than in 31 (31%) patients with rheumatic diseases (p=0.324). The rate of lung infiltration on radiographic examination was higher in patients without rheumatic diseases (40% vs. 49%) (p=0.177). COVID-19 infection symptoms such as anosmia 45 (45%), ageusia 51 (50%), shortness of breath 45(45%), nausea 29 (29%), vomiting 16 (16%), diarrhea 25 (25%) and myalgia-arthralgia 81 (80%) were higher in patients with rheumatic diseases. In terms of laboratory values, lymphocyte count (p=0.031) was statistically higher in patients without rheumatic diseases. Hydroxychloroquine (35%), oseltamivir 10 (10%), antibiotics 27 (26%), acetylsalicylic acid 52 (51%), and supplementary oxygen 25 (25%) treatments which used to cure COVID 19 infection were administered more in patients without rheumatic diseases. The number of treatments administered was higher in patients without rheumatic diseases (p<0.001). Conclusion: Patients with the chronic inflammatory-rheumatic disease have more symptoms due to COVID-19 infection, but the disease course is not poor and hospitalization rates are lower.